Analysis Of The Influence Of HR Competency, Implementation Of The Regional Financial Accounting System And Internal Control System On The Quality Of The Regional Government's Financial Reports In East Lombok Regency - Syawal Zakaria; Nicko Albart; Yudi Nur Supriadi; Aprih Santoso; Loso Judijanto (Jurnal Manajemen Pelayanan Publik, 2023)
The formulation of the problem is how does HR competency, implementation of the Regional Financial Accounting System and Internal Control System affect the quality of government financial reports? The research aims to analyze the influence of human resource competency factors, regional financial accounting systems, and internal control systems on the quality of regional financial reports in East Lombok Regency. The main theories are HRM Theory and Financial Reporting Quality Theory. This research uses quantitative methods. Data collection using a questionnaire. The sampling method is a census sampling technique with a population of 45 employees. Data were analyzed using IBM SPSS version 22, analysis using tests: validity, reliability, classical assumptions, linear regression analysis and coefficient of determination. The results of the research, human resource competency, implementation of SAKD, internal control systems influence the quality of regional financial reports at the East Lombok Regency BPKAD Office. In conclusion, the existence of positive interactions, increasing HR competency, implementing SAKD, and a good internal control system contributes to improving the quality of financial reports. These findings serve as a reference for local governments to improve the quality of financial reports which have a positive impact on public trust.